Aloe arborescens preparation and liver health - Anwar, Wagida A.; Kirjavainen, Pirkka V.; Isola, Jaana; El Zarka, Mohamed; Spiros, Tony Moros; El-Nezami, Hani (European Journal of Oncology and Environmental Health, 2009)
Aloe arborescens Miller var. natalensis Berger (so called as “ALOE”) is traditionally valued herbal medicine for gastrointestinal complaints, skin injuries and burns. The different pharmacological and therapeutic activities of ALOE have been studied. ALOE extracts have been reported to show anti-inflammatory, antidiabetic and antitumorigenic effects. In F344 rats, ALOE has been shown to have beneficial effects against colorectal tumorigenesis and formation of liver preneoplastic lesions. The aim of this study was to evaluate the effects of oral intake of ALOE preparation (Aloe arborescens, honey and distillate) on liver health. For this purpose, we investigated the effect of oral ALOE supplementation on the splenic and hepatic cellular immune functions in mice and on dimethylnitrosamine (DMN) – induced liver fibrosis in rats. The studied immune parameters included the presence and cytokine production of different T-cell populations, including T-cell helper (CD4+) subpopulations (Th1, Th2, Th17 and Tregs), cytotoxic T-cells (CD8+) and Natural Killer T (NKT) cells as well as Natural Killer (NK) cells. The anti-fibrogenic potential of ALOE was evaluated based on hepatic stellate cells (HSCs) activation and apoptosis due to DMN treatment. The most evident immunological effect associated with ALOE supplementation was the reduced prevalence of splenic NKT cells (p=0.02). In addition, the treatment appeared to increase the total proportion of CD4+ cells among splenic T cells (p=0.03) and the interferon-g production by hepatic Th1 cells (p=0.06) tented to increase. In DMN-treated rats, the ALOE supplementation reduced the hepatic hydroxyproline content and a-SMA expression and improved the histopathology compared to controls. These results indicate that ALOE administration may have immunomodulatory effects and lower the fibrogenic process in the liver.